Synthesis and serotonin transporter activity of 1,3-bis(aryl)-2-nitro-1-propenes as a new class of anticancer agents - MCNAMARA, YVONNE; WILLIAMS, DAVID; CLOONAN, SUZANNE; KNOX, ANDREW; MEEGAN, MARY (My University, 2011)
Structural derivatives of 4-MTA, an illegal amphetamine analogue have been previously shown to have anticancer effects in vitro. In this study we report the synthesis of a series of novel 1,3-bis(aryl)-2-nitro-1-propene derivatives related in structure to 4-MTA. A number of these compounds containing a classic nitrostyrene structure are shown to have antiproliferative activities in vitro in a range of malignant cell lines, particularly against Burkitt?s lymphoma derived cell lines, whilst having no effect on `normal? peripheral blood mononuclear cells. Such effects appear to be independent of the serotonin transporter, a high affinity target for amphetamines and independent of protein tyrosine phosphatases and tubulin dynamics both of which have been previously associated with nitrostyrene-induced cell death. We demonstrate that a number of these compounds induce caspase activation, PARP cleavage, chromatin condensation and membrane blebbing in a Burkitt?s lymphoma-derived cell line, consistent with these compounds inducing apoptosis in vitro. Although no specific target has yet been identified for the action of these compounds, the cell death elicited is potent, selective and worthy of further investigation.
PUBLISHED
Keywords: Biochemistry; Burkitt?s lymphoma; Cancer